MENATA KEMBALI KEDUDUKAN DAN FUNGSI “KONSEP SUCI AUDIT” DALAM HUBUNGANNYA DENGAN KINERJA AUDITOR DAN KUALITAS HASIL AUDIT (STUDI PADA INTERNAL AUDITOR INSPEKTORAT KABUPATEN / KOTA DI JAWA BARAT) - Didi, Didi; Widyastuti, Tri; Choirul, Anwar (Jurnal Akunida, 2021)
This study aims to examine how the “ holy concept of auditing” which consists of independence as a “state of affairs” and objectivity as a “state of mind” can improve auditor performance and audit quality. To explain these two things, this study proposes a mediation model that identifies how objectivity mediates between independence and auditor performance, how objectivity mediates between independence and audit quality, and how simultaneously objectivity and auditor performance mediate between independence and audit quality. The research method used is a survey method, namely: a research method that collects data by distributing questionnaires to samples that are used as respondents. The sampling technique was proportionate stratified random sampling, so that from 461 auditors who became the population of 27 Regency/City Inspectorates in West Java, 210 respondents would be sampled. The analysis tool uses Covariance Based Structural Equation Modeling (CBSEM) with the help of SmartPLS software version 3.0. The results of the study prove that: objectivity perfectly mediates between independence and auditor performance, objectivity perfectly mediates between independence and audit quality, and simultaneously objectivity and auditor performance perfectly mediates between independence and audit quality. Keywords: holy concept of auditing; audit performance, and audit quality;